Implementation of Performance Measurement Through the Balanced Scorecard (BSC) Method at Elementary Education Level (Case Study at Lengkong Bojongsoang Elementary School, Bandung Regency) - H. Soro , Suharyanto; E, Anwar; Hermawan, Wawan; Maryam, Maryam; Shofiyatul, Wafa (Global Education Journal, 2025)
Measurement is one of the instruments used to assess the performance of educational units. Measurement activities are one of the problems faced by assessors because they use indicators with a high level of accuracy. Implementation of four BSC perspectives—finance, customers (stakeholders), internal business processes, and learning and growth—in the context of elementary schools. This study aims to analyze the application of the Balanced Scorecard (BSC) method as a performance instrument at the elementary education level. The researcher used a case study approach. Respondents or samples in this study were principals and teachers. Respondents were selected purposively. The location of the study was SDN Lengkong Bojongsoang, Bandung Regency. The results showed that the BSC approach made a significant contribution to improving the quality of school management, although there were still challenges in understanding the concept and systemic integration.